Analisis Psikologi Tokoh Utama dalam Film Bumi Manusia Karya Pramodya Ananta Toer dan Relevansinya dengan Pembelajaran Bahasa Indonesia di SMA - Fitriani, Ellysa; Darmuki, Agus; Setiyono, Joko (Lentera: Jurnal Ilmiah Kependidikan, 2020)
a film type of literary work presented in scenes that make the literary connoissedly sound. The life problems of the main character can be shape by social problems of the main character. The earth man is one of those Indonesian films which tell of life during the colonization. Minke was native who wanted his people to end trheir sad fate. From the story of Minke above, reseacrhers will discuss the psychological state of the main character in the human film this study is conducted with the purpose of describing how psychology in the main character and its relevance in the Indonesian language of the high school. In analyzing this human earth film, reseacrhers used the psychological theory of Sigmud Frued using Id, Ego, Superego psychoanalysis. The study Uses qualitative descriptive reseacrh designs. Based on the result of the data analysis, four conculions were obtained from thye following reseacrh. The Minke earth man movie, judging by its soul structure, is more superego than ego and id human earth film is relevant from drama studies in the 11 th grade because it meets the standards of competence, basic competence and drama indicators found in silabus and RPP.